Peran Guru Pendidikan Agama Islam dalam Membina Akhlakul Karimah untuk Meningkatkan Kemandirian Peserta Didik SMA-IT Miftahul Khoir Dago Bandung - Amelia; Sobar Al Ghazal; Helmi Aziz (UNISBA Press, 2022)
Abstract. There were students who still did not practice good morals, while at SMA-IT Miftahul Khoir there was already moral development. So from that moment on, fostering moral character for the independence of students needs to be improved again so that students who have good morals are created and are able to become independent students. Fostering moral character to increase the independence of students in order to achieve it, it is necessary to know and understand the factors that influence moral development to increase independence so that the expected learning objectives can be achieved. Based on these conditions, the researcher is interested in researching